2007
DOI: 10.1016/j.soc.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Current Immunotherapeutic Strategies for Central Nervous System Tumors

Abstract: Immunotherapy has emerged as a promising tool in the management of malignant central nervous system (CNS) tumors. Despite the improvement in patient survival, traditional approaches -which consist mostly of surgery, radiotherapy, and chemotherapy -have been largely unsuccessful in permanently controlling these aggressive tumors. Immunotherapeutic strategies therefore offer not only a novel approach, but also an advantage in a way other modalities have been failing. Specifically, the capabilities of the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Some of these include immunotherapy, stem cell therapy, local chemotherapy and radiotherapy (Lesniak et al , 2001; Ehtesham et al , 2005; Lesniak, 2005; Kushen et al , 2007). Conditionally replicative adenoviruses (CRAds) represent a novel treatment strategy as well (Sonabend et al , 2006).…”
mentioning
confidence: 99%
“…Some of these include immunotherapy, stem cell therapy, local chemotherapy and radiotherapy (Lesniak et al , 2001; Ehtesham et al , 2005; Lesniak, 2005; Kushen et al , 2007). Conditionally replicative adenoviruses (CRAds) represent a novel treatment strategy as well (Sonabend et al , 2006).…”
mentioning
confidence: 99%
“…Recent studies using animal and EAE models have suggested that DCs may be important APCs involved in intracranial immunity. Further studies are necessary to elucidate the role of DC in antigen presentation in the setting of glioblastoma [576263]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical trial design-related issues incorporating novel therapeutic approaches will be discussed. Although immunotherapy approaches for the treatment of brain tumors are rapidly emerging and have shown some preliminary successes, this topic is beyond the scope of this article and has been recently reviewed elsewhere (Kushen et al, 2007).…”
mentioning
confidence: 99%